2007
DOI: 10.1007/s10761-006-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

Silent Voices, Hidden Lives: Archaeology, Class and Gender in the CMS Missions, Bay of Islands, New Zealand, 1814–1845

Abstract: This paper explores the themes and tensions of class and propriety at one of New Zealand's early European settlements, a Church Missionary Society mission in the Bay of Islands. Archaeological investigations at the site of the Te Puna mission house revealed a cellar containing, among other articles, items connected with domesticity and feminine concerns, demonstrating the presence of womenand their daily activities. The interweaving of the archaeological and historical record sheds light upon the replication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…This suggests that the Gordons at Dillon's Bay may have consumed more alcohol than their fellow missionaries. It has been suggested that alcohol consumption was one of many class markers viewed negatively in the CMS missions in New Zealand (Middleton 2007). It is not clear whether the same was true of the Presbyterian missions in the New Hebrides.…”
Section: G Gordon House Artefact Assemblagementioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the Gordons at Dillon's Bay may have consumed more alcohol than their fellow missionaries. It has been suggested that alcohol consumption was one of many class markers viewed negatively in the CMS missions in New Zealand (Middleton 2007). It is not clear whether the same was true of the Presbyterian missions in the New Hebrides.…”
Section: G Gordon House Artefact Assemblagementioning
confidence: 99%
“…An even richer archaeological literature of Christian expansion exists in the colonial context (e.g. Crossland 2006;Hiscock 2013;Lightfoot 2005;Lydon 2009;Lydon and Ash 2010;Middleton 2003Middleton , 2007Middleton , 2008Morrison et al 2015;Panich and Schneider, eds 2014;Smith 2014;Smith et al 2012;Wingfield 2013). …”
Section: Changing and Staying The Samementioning
confidence: 99%
“…Within the CMS and other evangelizing missions, the role of domesticity was of central importance; the position of women was idealized and emphasized in the "cult of true womanhood" or the "cult of domesticity" (Davidoff and Hall, 1991;Fitts 2001;Grimshaw, 1989aGrimshaw, , p. 22, 1989bJohnston, 2003;Langmore, 1989b;McClintock, 1995;Middleton, 2007a;2008b). Men were encouraged, and expected, to marry before moving into the mission field in order to demonstrate the model of ideal European gender roles and to save themselves from the perils of indigenous women (Gunson, 1978;Johnston, 2003;Middleton, 2007a;Murray 2000).…”
Section: The Evangelical Revival and The Church Missionary Societymentioning
confidence: 99%
“…Men were encouraged, and expected, to marry before moving into the mission field in order to demonstrate the model of ideal European gender roles and to save themselves from the perils of indigenous women (Gunson, 1978;Johnston, 2003;Middleton, 2007a;Murray 2000). While attendance at public meetings and similar events was deemed unacceptable for women, they were perceived as having a limited role in the public sphere, in the area of social reform and conversion to Christianity (Murray, 2000).…”
Section: The Evangelical Revival and The Church Missionary Societymentioning
confidence: 99%
“…The nature of the information means that the investigation can be focused on a specific individual, such as Little's (2007, pp. 99-101) narrative about Anne Catharine Green, or White's (2005White's ( , 2008) studies on the role of personal adornment in constructing identity (also see Middleton 2007). Though both archaeologists take a different tack-Little links her investigation to power and capitalism more than White, and White relies more than does Little on an interpretive approach that stresses social performance-both archaeologists understand that gender, like other vectors of social inequality, are constructs that are embedded within the sociohistorical context of the times.…”
Section: Vectors Of Inequalitymentioning
confidence: 99%